Global banking network and regional financial contagion - Cyn-Young Park; Kwanho Shin (Asian Development Bank (ADB), 2018)
This paper investigates and tests the role of regional exposures in financial contagion from advanced to emerging market economies through the global banking network using data on cross-border bilateral bank claims and liability positions. We first examine whether an economy can become more susceptible to capital outflows, regardless of its own bank exposures, if economies in the same region are heavily exposed to crisis countries. Second, we test whether the same region lenders tend to reduce exposures to the emerging market borrowers less than do different region lenders during crises. Using bilateral data from the Bank for International Settlements international banking statistics, we obtain evidence for both hypotheses. First, we find that direct exposures of a country's own and the overall region's banking sectors to crisis-affected countries are systematically related to bank capital outflows during the global financial crisis. Also, some of our empirical results indicate that an emerging economy's financial vulnerability can be influenced by its region's indirect exposures to crisis countries. Second, a further analysis suggests more favorable behavior of the same region lender toward emerging economies during crisis.
Keywords: E44; F15; F21; F34; F38; F42; F62; 330; capital outflows; contagion; direct/indirect exposures; global financial crisis; regional